PENGARUH MANAJEMEN LABA, UKURAN KAP DAN LEVERAGE TERHADAP BIAYA AUDIT PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Ayu Primasari; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of earnings management, audit firm size and leverage towards audit fees on manufacturing companies in Indonesia. This study uses secondary data which obtain from Indonesia Stock Exchange during the year of 2013-2015. The populations in this study are 413 companies which listed on Indonesia Stock Exhange. The selected companies that used to be sample of this study are manufacturing companies that consist of basic industry and chemical sector, all sorts of industry sector and consumer goods industry sector. Based on criterias which had been assigned, the samples of this study are 118 manufacturing companies. The method of analysis used in this study is multiple regression analysis. The results show that earnings management and audit firm size have a positive effect towards audit fees. Meanwhile, leverage has a negative effect towards audit fees.